The Effect of Surgical Decompression and Fusion on Functional Balance in Patients With Degenerative Lumbar Spondylolisthesis. Issue 14 (15th July 2020) - Haddas, Ram; Lieberman, Isador; Block, Andrew; Derman, Peter
Abstract : Study Design: Prospective cohort study. Objective: To quantify the effect of lumbar decompression and fusion surgery on balance and stability in patients with degenerative lumbar spondylolisthesis (DLS) and compare them to controls. Summary of Background Data: DLS is a condition in which one vertebra subluxates relative to an adjacent vertebra in the absence of a disruption in the neural arch. While the existing literature demonstrates that decompression and fusion can successfully alleviate pain and reduce disability in patients with DLS, no studies to date have used quantitative dynamic testing to determine the effect of surgery on cone of economy (CoE) measures in this patient population. Methods: Forty-five DLS patients performed a series of functional balance tests a week before and 3 months after surgery and were compared to 28 controls. The outcome measures included range of sway (RoS) and total sway for the center of mass (CoM) and head in the sagittal, coronal, and axial planes, along with leg and back Visual Analog Scale (VAS), Oswestry Disability Index (ODI), Fear/Avoidance Behavior Questionnaire (FABQ), Tampa Scale of Kinesophobia (TSK), and Demoralization scale. Results: RoS for the CoM ( P  < 0.005) and head ( P  < 0.017) decreased in all planes postoperatively. Reductions in CoM ( P  = 0.001) and head total sway ( P  = 0.001) were also observed after surgery. Furthermore, patients with DLS reported strong improvements in VAS low back ( P  = 0.001), VAS leg ( P  = 0.001), ODI ( P  = 0.001), FABQ Physical ( P  = 0.003), TSK ( P  = 0.001), and demoralization ( P  = 0.044) with surgical intervention. Although total sway was reduced after surgery, it did not return to the level of normal controls as demonstrated with more total sway of their CoM ( P  = 0.002) and head ( P  = 0.001) as well as more sagittal head RoS ( P  = 0.048). Conclusion: This study confirms that surgical intervention for degenerative spondylolisthesis is effective at reducing disability, back and leg pain, demoralization, kinesiophobia, and fear-avoidance beliefs related to physical activity in patients with DLS. Furthermore, such patients exhibit a significantly more stable stance after surgery. However, balance parameters did not completely normalize by 3 months postoperatively. Level of Evidence: 3 Abstract : Forty-two degenerative lumbar spondylolisthesis patients performed a series of functional balance tests a week before and 3 months after surgery. They were compared to 26 controls. Surgical intervention improved balance and stability, reduced disability, and improved patient-reported outcomes. However, balance parameters did not completely normalize by 3 months postoperatively.